Penerapan Model Regresi Log-Binomial untuk Menduga Risiko Relatif Kemacetan Kredit Berdasarkan Karakteristik Debitur - Risma Nur Ismayani; Abdul Kudus (Bandung Conference Series: Statistics, 2023)
Abstract. Relative risk is the ratio of odds between binary exposures or the ratio of odds between the exposed and unexposed groups. The concept of relative risk is often introduced in a simple way, using a 2 x 2 cross tabulation of binary exposure and binary outcome. Then go further with the use of regression to estimate relative risk. A log-binomial regression model has been recommended which can directly estimate relative risk. The data used is data on credit debtors for Bhakti to determine the ratio of the risk of credit default based on the characteristics of the debtor using a log-binomial regression model. The results of this study obtained a log-binomial regression model is π = (-1,1032640 -0,6335250x1 + 1,0977941x2 - 0,3544660x3 - 1,2765607x4 + 1,7367890x5 + 1,0244938x6). The relative risk outcomes using the log-binomial regression model based on significant interval estimates were the number of dependents (RR=3.00; 95%Cl 1.68-5.36), employment status ( RR=0.28; 95%Cl 0.16-0.48), debtor type (RR =5.68; 95%Cl 3.47-9.31) and length of working (RR =2.79; 95%Cl 1.46-5.33) meaning that if the number of group members compared is the same, then, 1) in the group of dependents ≤ 2 people there are 300 debtors who experience credit missed payment, while in the group of dependents > 2 there are only 100 debtors who are in missed payment, 2) in the group of permanent employees there are 28 who are in missed payment, while in the CPNS group there are 100 who are in missed payment, 3) in the group of new debtors there are 568 who are in missed payment, while in the group of repeat debtors there are only 100 debtors who are in missed payment, and 4 ) in the group of debtors who worked ≤ 2 years there were 279 missed payment, while those who had worked > 2 years there were 100 missed payment debtors. Abstrak. Risiko relatif adalah perbandingan peluang antara paparan biner atau perbandingan peluang antara kelompok yang terpapar dan kelompok yang tidak terpapar. Konsep risiko relatif sering kali diperkenalkan dengan menggunakan cara yang sederhana yaitu menggunakan tabulasi silang dari paparan biner dan hasil biner. Lalu lebih lanjut lagi dengan menggunakan penggunaan dari regresi untuk menduga risiko relatif. Model regresi log-binomial telah direkomendasikan yang secara langsung dapat menduga risiko relatif. Data yang digunakan adalah data debitur kredit Guna Bhakti untuk mengetahui perbandingan risiko kemacetan kredit berdasarkan karakteristik debitur menggunakan model regresi log-binomial. Adapun hasil penelitian ini diperoleh model regresi log-binomial yaitu π = (-1,1032640 -0,6335250x1 + 1,0977941x2 - 0,3544660x3 - 1,2765607x4 + 1,7367890x5 + 1,0244938x6). Hasil risiko relatif menggunakan model regresi log-binomial berdasarkan taksiran interval yang signifikan adalah jumlah tanggungan (RR =3,00 ; 95%Cl 1,68-5,36), status kepegawaian ( RR=0,28; 95%Cl 0,16-0,48), tipe debitur ( RR=5,68; 95%Cl 3,47-9,31) dan lama kerja ( RR=2,79; 95%Cl 1,46-5,33) artinya jika jumlah anggota kelompok yang dibandingkan besarnya sama maka, 1) pada kelompok jumlah tanggungan ≤ 2 orang terdapat 300 debitur yang mengalami kemacetan kredit, sedangkan pada kelompok jumlah tanggungan > 2 hanya ada 100 debitur yang macet, 2) pada kelompok pegawai tetap terdapat 28 yang macet, sedangkan pada kelompok CPNS terdapat 100 yang macet, 3) pada kelompok debitur baru terdapat 568 yang macet, sedangkan pada kelompok debitur yang mengulang hanya terdapat 100 debitur yang macet, dan 4) pada kelompok debitur yang bekerja ≤ 2 tahun terdapat 279 yang macet, sedangkan yang sudah bekerja > 2 tahun terdapat 100 debitur yang macet.